KEPASTIAN HUKUM GADAI TANAH DALAM HUKUM ISLAM (TELAAH HUKUM GADAI ISLAM TERHADAP PELAKSANAAN GADAI TANAH DI KABUPATEN BOGOR) - Muhammad Sulaeman Jajuli (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2017)
Fiduciary is a usual universal sociological phenomenon that occur everywhereespecially in our country. In Indonesia society, it grows conventionally and based on habit that have occurred for generation to generation. Land fiduciary in Bogor district has done for long time. Practice of land fiduciary that occurred was running without any document for legal certainty guarantee. Meanwhile, academically legal certainty guarantee is a theory that has not been developed yet by Islamic law jurist. Based on research results, concluded that 1. Implementation of rule according to Islamic law fiduciary land must meet the requirements and harmonious elements of fiduciary. Terms pledge the land is; can be handed over, useful, or fixed assets can be moved, not mixed up with someone else's property, and land is fiduciary owned by râhin. The pillars pledge is âqid (presence of râhin and murtahin), al-ma'qûd (marhun), al-ma'qûd 'alaih (marhûnbih) and shîghat. Practice fiduciary land in legal term in Islam is called bay al- wafa' not rahn because the terms and pillars contained in rahn accordance with the rules in bay al-wafa. 2. The definition of legal certainty in the implementation of fiduciary land under Islamic law is evidence in the form of written documents in the form of stamp duty, or paper sealed and the presence of witnesses from both parties’ murtâhin and râhin. For the Bogor regency society,legal certainty is considered sufficient to the existence of an element of trust between two sides (murtahin and râhin) without the use of evidence or documents and witnesses. 3. Based to the study of the law of Islamic fiduciary land, practices of fiduciary land in Bogor regency society belong to the category imperfect contract. Said to be imperfect because of the implementation agreement contained elements of usury which is forbidden by the religion that is taking advantage of more than possession lent. Besides the practice of fiduciary in Bogor regency become less perfectly even invalid because it is contrary to the commands of Allah in the ◌Al-Qur'an about the principle of 'faktubuh' (Surah al-Baqarah/2:282) Key Word: Kepastian Hukum, Hukum Islam, Gadai Tanah, Bogor